Вы находитесь на странице: 1из 6

6. .

.
1.

. sin x cos x ,

(, , )
R ( sin x;cos x ) , R .

R ( sin x; cos x ) dx

tg

x
= t ,
2

.
x
1 tg 2
2
, cos x =
sin x =
2 x
1 + tg
1 + tg 2
2

2tg

sin x =

2t
1+ t

, cos x =

1 t2
1+ t

x
2 , x = 2arctgt , dx = 2 dt ,
x
1+ t2
2

, x = 2arctgt , dx =

2dt
1+ t2

2t 1 t 2 2
R
sin
x
;
cos
x
dx
R
=
(
)

1 + t 2 ; 1 + t 2 1 + t 2 dt = R1(t )dt , R1(t )

t .
.

dx

1 + sin x + cos x .

x
2dt
2t
t = tg . dx =
, sin x =
,
2
2
1+ t
1+ t2
cos x =

1 t2
1+ t2

. ,

2dt

dx

1 + sin x + cos x =

1 t2

(1 + t 2 ) 1 + 1 +2tt 2 + 1 + t 2

dt
=
t +1

d ( t + 1)
x
= ln(t + 1) + C = ln(tg + 1) + C.
t +1
2

,
, ,
. ,
, ( ) .
, :

1)

R ( sin x;cos x )

sin x ,

..

R ( sin x;cos x ) = R ( sin x; cos x ) , cos x = t ;


2)

R ( sin x;cos x )

cos x ,

..

R ( sin x; cos x ) = R ( sin x; cos x ) , sin x = t ;


3)

R ( sin x;cos x )

sin x

cos x

R ( sin x; cos x ) = R ( sin x;cos x ) , tgx = t .


,

R ( sin

x;cos 2 x dx :

sin 2 x =

t2
1+ t

, cos 2 x =

x = arctgt ,

. I =

R( sin x; cos x) =

, tgx = t ,
1+ t2
dt
dx =
1+ t2

dx
3 + sin 2 x

1
3 + ( sin x )

1
3 + sin 2 x

= R ( sin x; cos x ) ,

tg x = t .

x = arctg t , dx =

R(tgx)dx

dt
1+ t2

sin 2 x =

tg 2 x
1 + tg 2 x

t2
1+ t2

I =

dt

t2
1+ t2 3 +

1+ t2

2 3

2.

dt
4t 2 + 3

d ( 2t )
1
=

2 ( 2t )2 + ( 3)2

2t
1
2

+C =
arctg
tgx + C.
3
2 3
3

arctg

sin

x cos n xdx

1) sin x = t , n .
2) cos x = t , m .
1
cos 2 x = (1 + cos 2 x) ,
2

3) :

sin 2 x =

1
(1 cos 2 x) ,
2

1
sin x cos x = sin 2 x , m n .
2

4) tg x = t , m + n .

dx

sin m x

d 2x

2m 1 sin m 2x cos m 2x

dx

cosm x

d x + 2

sin m x + 2

1) , m n , :

sec2 x =

= tg 2 x + 1 ,

cosec2 x =

cos x

6) ,

1
2

= ctg 2 x + 1 .

sin x

(
):

sin

x cos n xdx = sin m x cos n 1 x cos xdx =

= sin m x 1 sin 2 x

n 1
2

d sin x = t m 1 t 2

n 1
2

dt .

.
1. I = sin 3 x cos 2 xdx.
m = 3 . cos x = t . x = arccos t ,
dx =

1
1 t

dt , sin x = 1 t 2

3
dt

2 2
I = 1 t t

1 t 2

= (1 t 2 )t 2 dt = t 4 t 2 dt =

1
1
t5 t3
+ C = cos5 x cos3 x + C.
5 3
5
3

2. I = sin 2 x cos 4 xdx.


m = 2, n = 4 .

1
1
I = (sin x cos x)2 cos 2 xdx = sin 2 2 x (1 + cos 2 x)dx =
4
2

1
1
sin 2 2 xdx + sin 2 2 x cos 2 xdx =

8
8

1 1
1
(1 cos 4 x)dx + sin 2 2 xd (sin 2 x) =

8 2
16

3. I =

1
1
1
x sin 4 x + sin 3 2 x + C.
16
64
48

dx
3

cos x sin x

= cos 1 x sin 3 xdx.

m + n = 4 . tgx = t . x = arctg t , dx =

cos x =

1
1+ t

dt
1+ t

, sin x =

t
1+ t

dt
I =

1+ t2
1

1+ t2
t

dt = t 3dt +

dt
=
t

1+ t2 1+ t 2

1
+ ln t + C = ctg 2 x + ln tgx + C.
2
2t
2

4. I =

dx
cos 4 x

I =

1
dx = tg 2 x + 1 d ( tgx ) = tg3 x + tgx + C .
3
cos 2 x cos 2 x

3.

sin ax cos bx , cos ax cos bxdx , sin ax sin bxdx

sin cos =

1
( sin ( ) + sin ( + ) ) ,
2

cos cos =

1
( cos ( ) + cos ( + ) ) ,
2

sin sin =

1
( cos ( ) cos ( + ) ) .
2

. I = cos 3 x sin 7 xdx .

I = cos 3 x sin 7 xdx =

1
( sin 4 x + sin10 x ) dx =
2

1 1
1

= cos 4 x cos10 x + C .
2 4
10



.
:

ch 2 x sh 2 x = 1 ,

ch 2 x =

1
sh 2 x = (ch2 x 1) ,
2

1
(ch2 x + 1) ,
2

1
shx chx = sh2 x .
2

. I = ch 3 xdx.
I = ch x chxdx =
2

sh 3 x
1 + sh x dshx = shx +
+C .
3